Aspectos históricos, filosóficos e sociológicos do sistema periódico dos elementos químicos: implicações para o ensino de Química - Romero, Adriano Lopes (2021)
The periodic system, a scientific construct developed by the contribution of various chemistry practitioners, organizes chemical elements based on the periodic law and is represented by a graphical representation. Its initial development took place in the 1860s, with the aim of reducing the plurality of accumulated knowledge about chemical elements, and gained explanatory power as new knowledge was produced in Chemistry and Physics, such as those related to atomic structure and quantum mechanics. It is a structuring knowledge for both chemistry practitioners and for the Chemistry school subject. In this sense, we seek to understand the development, socialization and appropriation of knowledge related to the periodic system, by chemistry practitioners, from different perspectives on this object of study. Based on a historiographical study, we found that, despite the existence of several graphic representations of the periodic system, the periodic table recommended by IUPAC has become the representation most used by chemistry practitioners. By naturalizing itself as a scientific fact, the periodic table came to be considered, in a broad sense, synonymous with the periodic system and became a school content at different levels of education. This naturalization process, however, is not explicit in chemistry textbooks, which bring a history of the periodic table consisting of historical fragments presented chronologically and full of anachronisms. These historical fragments are generally related to the initial development of the periodic system in the 1860s and to (or as a consequence of) Moseley's work in the 1910s, which resulted in the knowledge of atomic numbers. The tendency of the history of science to become more whig as it becomes more summarized was verified in the textbooks evaluated. This trend contributed to the emergence of hagiography, for example the one that considers the historical agent Mendeleev the main creator or the only creator of the periodic table, depending on the level of whiggism present in the historical content, as well as contributed to the (almost) erasure of the others historical agents related to the development of the periodic system. As a school content, the periodic table is understood as a tool, a black box, aspects related to the system it represents are not discussed (or superficially discussed), so its limitations/problems are considered exceptions or not discussed. From the reflections made throughout the thesis, we glimpse some implications for the teaching of Chemistry, such as the need for changes in the initial and continuing education of teachers and the approximation of differences in areas in which chemical knowledge is an object of study, which implies in an individual effort of the active teacher in Basic Education, a collective effort of the teacher-trainers and a collective effort in the area of Education in Chemistry.